2014
DOI: 10.1371/journal.pgen.1004349
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Four Glycosyl Hydrolases Reveal a Highly Coordinated Pathway for Rhodopsin Biosynthesis and N-Glycan Trimming in Drosophila melanogaster

Abstract: As newly synthesized glycoproteins move through the secretory pathway, the asparagine-linked glycan (N-glycan) undergoes extensive modifications involving the sequential removal and addition of sugar residues. These modifications are critical for the proper assembly, quality control and transport of glycoproteins during biosynthesis. The importance of N-glycosylation is illustrated by a growing list of diseases that result from defects in the biosynthesis and processing of N-linked glycans. The major rhodopsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 91 publications
2
31
0
Order By: Relevance
“…This was accomplished by monitoring the molecular weight of Rh1 via Western blot analysis. We have previously shown that Rh1 is glycosylated in the ER and then completely deglycosylated as it moves through the Golgi, such that defects in Rh1 transport lead to the accumulation of Rh1 in hyperglycosylated high molecular weight forms (39,47). The gos28 1 EMS allele displayed a defect in Rh1, with a substantial amount of the protein accumulating in a higher molecular weight form, compared with wild type (Fig.…”
Section: Identification Of Mutations In Drosophila Gos28mentioning
confidence: 90%
See 4 more Smart Citations
“…This was accomplished by monitoring the molecular weight of Rh1 via Western blot analysis. We have previously shown that Rh1 is glycosylated in the ER and then completely deglycosylated as it moves through the Golgi, such that defects in Rh1 transport lead to the accumulation of Rh1 in hyperglycosylated high molecular weight forms (39,47). The gos28 1 EMS allele displayed a defect in Rh1, with a substantial amount of the protein accumulating in a higher molecular weight form, compared with wild type (Fig.…”
Section: Identification Of Mutations In Drosophila Gos28mentioning
confidence: 90%
“…mutant, we screened ϳ12,000 ethyl methylsulfonate (EMS) mutagenized lines from the Zuker collection (37) for the presence or absence of the deep pseudopupil (38). We identified ϳ900 deep pseudopupil-defective mutants, which were further screened for defects in Rh1 by Western blot analysis (39). The wild-type stocks used in this study were bw;st and cn,bw (parental stocks from the EMS mutagenesis), as well as Canton-S. We also used the eyes absent mutant allele, eya 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations